American Television News : the Media Marketplace and the Public Interest. - Barkin, Steve M. (Taylor and Francis, 2002)
This book is an effort to tell the story of the last twenty-five years of television news in the context of the social and cultural history of American broadcasting. "Trash television" does not emerge from a vacuum; neither do broadcasts of the highest quality.